The castle in the attic - Winthrop, Elizabeth; Hyman, Trina Schart, ill. (New York : Scholastic, 1994)
A gift of a toy castle, complete with silver knight, introduces William to an adventure involving magic and a personal quest.
Keywords: Castles -- Fiction